2 answers:
<span>Simplifying
(7 + -2x)(11 + -2x)(x) = 0
Reorder the terms for easier multiplication:
x(7 + -2x)(11 + -2x) = 0
Multiply (7 + -2x) * (11 + -2x)
x(7(11 + -2x) + -2x * (11 + -2x)) = 0
x((11 * 7 + -2x * 7) + -2x * (11 + -2x)) = 0
x((77 + -14x) + -2x * (11 + -2x)) = 0
x(77 + -14x + (11 * -2x + -2x * -2x)) = 0
x(77 + -14x + (-22x + 4x2)) = 0
Combine like terms: -14x + -22x = -36x
x(77 + -36x + 4x2) = 0
(77 * x + -36x * x + 4x2 * x) = 0
(77x + -36x2 + 4x3) = 0
Solving
77x + -36x2 + 4x3 = 0
Solving for variable 'x'.
Factor out the Greatest Common Factor (GCF), 'x'.
x(77 + -36x + 4x2) = 0
Factor a trinomial.
x((7 + -2x)(11 + -2x)) = 0
</span>
-x-7=-2x-11
+7 +7
-x= 2x-4
+2x+2x
x=-4
You might be interested in
Answer
11 over 16
Step-by-step explanation:
i have no explanation but i got it right
Answer:
c
Step-by-step explanation:
Answer:
ill try
Step-by-step explanation: